2019
DOI: 10.1369/0022155419882292
|View full text |Cite
|
Sign up to set email alerts
|

CTLA-4 Immunohistochemistry and Quantitative Image Analysis for Profiling of Human Cancers

Abstract: There is an important need in immuno-oncology to develop reliable immunohistochemistry (IHC) to assess the expression of CTLA-4+ tumor-infiltrating lymphocytes in human cancers and quantify them with image analysis (IA). We used commercial polyclonal and monoclonal antibodies and characterized three chromogenic cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) assays with suitable specificity and sensitivity for use in formalin-fixed, paraffin-embedded (FFPE) tissues. We found variable numbers of CTLA-4+ ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…Most of the available data on CTLA-4 expression is limited to human T cells. Accordingly, we found that immunolabeling CTLA-4 with the antibody clone CAL49 vs. T lymphocytes markers CD3, CD4, and CD8 showed that CTLA-4(+) T lymphocytes in tonsils were typically CD3(+) and CD4(+), but not CD8(+), as was earlier reported by Brown et al [26]. However, cells that were immunostained with antibodies to the CTLA-4 (UMAB249 clone) were predominantly detected in the extrafollicular regions of the tonsil epithelium-both in the reticular epithelium and in the integumentary stratified squamous non-keratinized epithelium-but not in T-lymphocytes.…”
Section: Discussionsupporting
confidence: 86%
“…Most of the available data on CTLA-4 expression is limited to human T cells. Accordingly, we found that immunolabeling CTLA-4 with the antibody clone CAL49 vs. T lymphocytes markers CD3, CD4, and CD8 showed that CTLA-4(+) T lymphocytes in tonsils were typically CD3(+) and CD4(+), but not CD8(+), as was earlier reported by Brown et al [26]. However, cells that were immunostained with antibodies to the CTLA-4 (UMAB249 clone) were predominantly detected in the extrafollicular regions of the tonsil epithelium-both in the reticular epithelium and in the integumentary stratified squamous non-keratinized epithelium-but not in T-lymphocytes.…”
Section: Discussionsupporting
confidence: 86%
“…In recent years, the development of imaging analysis algorithms has mainly focused on positivity and intensity determination for cancer-associated biomarkers in IHC specimens. The few studies that were involved in the development of automatic TIL number measurements are shown in Table II (24)(25)(26)(27)(28)(29)(30)(31).…”
Section: Figure 6 the Significant Correlation Between The Manual Counting And Automatic Counting In Cd8 + Or Pd-1 + T Cell Measurements Omentioning
confidence: 99%
“…Brown et al reported that image analysis scoring based on a color deconvolution algorithm was highly comparable with pathologist scoring for CTLA-4 and CTLA-4/FoxP3 staining of regulatory T cells (24). Meanwhile, Yoo et al demonstrated that machine-learning-based image analysis such as QuPath can be useful for extracting quantitative information about the TMIT (tumor microenvironment immune types) using wholeslide histopathologic images (25).…”
Section: Figure 6 the Significant Correlation Between The Manual Counting And Automatic Counting In Cd8 + Or Pd-1 + T Cell Measurements Omentioning
confidence: 99%
“…63 The challenges of segmenting nuclei using the deep learning module included prolonged processing times and difficulty in correctly determining nuclear borders. 2,3 To decrease up to 1 hr per digital image processing time required for deep learning segmentation, uniform random sampling of the WSDI was performed (Fig. 6B).…”
Section: Less Precise Than Stereologymentioning
confidence: 99%
“…Advances in reagents, methodologies, analytic platforms, and tools have resulted in a dramatic transformation of the research pathology laboratory. 1,2 The development of digital cameras, computer hardware and software, and microscopes that convert stained tissue sections on glass slides into high-resolution whole slide digital images (WSDIs) has been central to these advances. Access to WSDIs, which can be viewed over the Internet using virtual microscopy, has resulted in the growth of the subfield of digital pathology, a paradigm shift in the pathology laboratory.…”
Section: Introductionmentioning
confidence: 99%